Distributed Generation, Storage and Active Network Management - Parthasarathy, Chethan; Khajeh, Hosna; Firoozi, Hooman; Laaksonen, Hannu; Hafezi, Hossein (CRC Press, 2022)
In this chapter, an overview of distributed generation, i.e. their classification and role in ANM of smart grid operations and adjoining control methodologies, will be addressed in detail. Energy storage systems play a crucial role as flexible energy resources for ANM in smart grids. Their technology types and various applications they tend to use will be explained. Battery energy storage systems (BESSs), especially Lithium-ion batteries with their current technology and economic maturity, are considered as a viable option for stationary grid applications. Design and control of Li-ion battery integration by means of power electronic converters for ANM in medium voltage distribution system, along with managing other flexibility services of DGs, are the scope of this chapter.
Keywords: active network management; battery energy storage systems; distributed generation; energy management methods; energy storage systems; flexible energy resources; fi=Sähkötekniikka|en=Electrical Engineering|